Quality education and the role of the teacher in Fiji: mobilising global and local values - Crossley, Michael; Frances, Cresantia; Vaka’uta, Koya; McGrath, Simon; Thaman, Konai Helu; Waqailiti, Ledua (Taylor & Francis, 2017)
This article reports on the findings of original field research carried out in the small island developing state of Fiji, in the South Pacific. A North-South research partnership was built upon previous collaboration between team members and, in so doing, pioneered the blending of Pacific and Western research approaches sensitive to a postcolonial positioning. The study interrogates practitioner perspectives on the nature and quality of teachers and teaching in Fiji; the challenges of teachers’ work and lives; priorities for successful qualitative reform; and theoretical implications for the processes of education policy transfer and qualitative improvement. The analysis draws upon work on the politics of aid and international development, revealing tensions between existing learner-centred policy frameworks and emergent neoliberal and performativity oriented initiatives influenced by international surveys of student achievement, related league tables and the experience of the regional reference societies of Australia, New Zealand and India.